ICON, SYMBOL, INDEX AND PRIMARY SIGNIFIER DESCRIBED IN SHAKESPEARE’S – HAMLET - Haryati Sulistyorini (Fakultas Ilmu Budaya, Universitas Dian Nuswantoro, 2008)
This paper describes icon, symbol, index, and primary signifier in one of the famous Shakespeare’s works, Hamlet. The analysis begins by describing the basic narrative structure, icon, symbol and index which is found in this play. Then it also describes the syntagmatic and paradigmatic dimension to find two different things between good and bad. From the result of the analysis it can be found that the primary signifier on Shakespeare’s Hamlet is Hamlet that symbolized the good things; honesty and loyalty. This can not be changed by the bad things; dishonesty, greediness as symbolized on Claudius.Keywords: icon, symbol, index and primary signifier